Official inauguration of the CTA building in Wageningen by HRH Prince Claus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
In 1 9S5 the Technical Centre for Agricultural and Rural Cooperation was inaugurated in Ede. Now CTA has moved closer to the centre of excellence in Agricultural Sciences that Wageningen represents, and on 19 April, 1996 the new building was...